Safety assessment of Acori Tatarinowii Rhizoma: acute and subacute oral toxicity - Liu, Jia; Ping, Xin; Sun, Shu-jie; Yang, Jiali; Lu, Ye; Pei, Lin (Frontiers in Pharmacology, 2024)
Acori Tatarinowii Rhizoma (ATR) is a well-known traditional Chinese medicine that is used for treating neuropathic diseases. However, there is little information about the safety of ATR. The present study evaluated the acute and subacute oral toxicity of a water extract of ATR in Institute of Cancer Research (ICR) mice. In acute trials, a single administration of extract at a dose 5000 mg/kg body weight led to no clinical signs of toxicity or mortality, indicating that the lethal dose (LD50) exceeded 5000 mg/kg. A subacute toxicity test was done using daily doses of 1250, 2500, and 5000 mg/kg of the ATR extract for 28 days, which did not show any adverse clinical symptoms or mortality. However, the male renal organ index and urea level in mice given 5000 mg/kg was obviously abnormal, which was consistent with pathological results and suggested that this dose might cause kidney injury. The results showed that doses of ATR lower than 2500 mg/kg could be regarded as safe, although the potential cumulative effects of long-term use of high doses of ATR need to be considered. The study highlights the function of ATR in reducing blood lipids and provides a new idea for its widespread clinical use in the future.